Examining Malaysian Hotel Employees Organizational Commitment by Gender, Education Level and Salary - Ariffin, Hashim Fadzil; Ha, Norbani Che (UI Scholars Hub, 2015)
The purpose of this study is to investigate the Organizational Commitment (OC) among Malaysian hotel employees. The aim is to identify the perception of employees concerning OC that they have perceived at their workplace and, how gender, education level and range of salary affect them. The data have been collected through sets of questionnare answered by 624 respondents who are hotel employees in Malaysia. The dimensions of OC which are affective, continuance and normative have been analysed using exploratory factor analysis (EFA). The data then been analysed using t-test and analysis of variance (ANOVA) to find the significance differences between gender, level of education and salary scale with the three dimensions of OC. The result of this study reveals that there is no significant diffrences between three dimensions of OC and gender. Findings also show that there are significant differences between education level and three dimensions of OC. Similarly, the results also display significant differences between salary scale and, affective and continuance commitment but not with normative comitment. Managerial implications, limitations and future research directions are also discussed.